Manajemen Fatigue melalui Kombinasi Aerobik dengan Relaksasi Yoga pada Penderita Kanker Payudara dalam Program Kemoterapi - Muhammad Taukhid (coba, 2017)
Background : Fatigue is feeling tired physically, psychologically, cognitively perceived cancer patients while undergoing therapies for the disease, including chemotherapy. The purpose of this study was to determine differences in the level of fatigue in cancer patients between before and after aerobic exercise combined with relaxation techniques of yoga. Methods : This study used Quasi-experimental design with pretest-posttest control group in patients with breast cancer in the course of chemotherapy. The sampling methods used purposive sampling. The fatigue level was collected by subjective instruments Pipper Fatigue Scale (PFS), and then analyzed by the Independent and Dependent T test, and multivariate analysis used linear regression with a significance value of α <0.05. Results : There were differences in the level of fatigue post-test between the intervention group and the control group with a difference of 1.25 (p = 0.013). History of previous exercise may explain the 17.8% level of fatigue that occurs in patients with breast cancer in the course of chemotherapy, the rest was explained by other variables. Conclusion : There were a decrease in the level fatigue statistically, however clinically the level of fatigue remain the same catagories. Keywords : fatigue, aerobic, yoga, breast cancer